Second and final report of the wages and salaries review commission, 1970-71 - Federal Ministry of Information, Nigeria (Lagos: Federal Ministry of Information, 1971)
The report recommends that certain measures should be taken to correct or curb the existing extraordinary inflationary situation, and that an interim monetary award, in the nature of a cost of living allowance should be made aimed at :relieving intolerable suffering at or near the bottom of the wage and salary levels".
rpm 15/02/2019
Arch
Keywords: Wages and Salaries; Nigeria